Multifunctional PtCuTe Nanosheets with Strong ROS Scavenging and ROS-Independent Antibacterial Properties Promote Diabetic Wound Healing - Guo, Yaru (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2023 Wiley-VCH GmbH.